Magnetic micro-protrusion arrays with wrinkled polypyrrole surfaces for enhancing the performance of flexible pressure sensors - Ruixue Sun; Jie Lu; Pei Li; Pingan Yang; Jianchun Jiang; Mengjie Shou; Changrong Liao (APL Materials)
Flexible sensing technology has been developed and improved rapidly in recent years, attracting widespread attention and research. Magnetic composites have great potential in the field of flexible sensing due to their excellent conductivity and magnetic controllability. Here, a performance enhanced flexible double-layer piezocapacitive sensor, PPy-SMPA, was proposed. The sensor consists of a substrate with surface micro-protrusion arrays formed by magnetic materials and a wrinkled PPy sensitive layer polymerized by chemical deposition. The internal micro-capacitance model of the sensor at different pressures was constructed, and the effects of the distribution degree of magnetic particles and the aspect ratio of the micro-protrusion on the equivalent capacitance were discussed. The sensor exhibited excellent cyclic stability, dynamic characteristics, and mechanical durability, with sensitivity reaching five times that of the planar substrate sensor in the low pressure range. On this basis, sensing arrays and grip strength tests were performed to accelerate practical development, and these sensors were integrated into smart insoles for fall detection early warning, demonstrating their potential applications in wearable devices, smart homes, and human health monitoring.